ABOUT INFLUENCE OF ORBITAL DYNAMIC RESONANCES FOR PECULARITY OF STATISTICAL ARRANGEMENT OF ASTEROIDS AND COMETS - Mushailov, B. R.; Teplitskaja, V. S. (Одеські астрономічні публікації, 2017)
Some regularities in organization of comet's and asteroid's orbital characteristics were described. These objects dispose from 5 to 125 a.u. from Sun. It was established that more than half of them move according to resonance orbits, which were predicted earlier.